Evaluation of the preschool life skills program in Head Start classrooms: A systematic replication. Issue 2 (11th May 2014) - Hanley, Gregory P.; Fahmie, Tara A.; Heal, Nicole A.
<x xml:space="preserve">Abstract</x> In an attempt to address risk factors associated with extensive nonfamilial child care, we implemented the preschool life skills (PLS) program (Hanley, Heal, Tiger, & Ingvarsson, 2007) in two community‐based Head Start classrooms. A multiple baseline design across classrooms, repeated across skills, showed that the program resulted in a 5‐fold increase in PLS and an accompanying reduction in problem behavior, replicating the effects observed by Hanley et al. (2007).